Prevalence of extended spectrum beta-lactamase in Klebsiella pneumoniae - Herwana, Elly; Yenny, Yenny; Pudjiadi, Laurentia; Surjawidjaja, Juius E; Lesmana, Murad (Universa Medicina, 2008)
Increased irrational use of antibiotics promotes bacterial resistance to these drugs. Among the resistance mechanisms developed by bacteria is the production of â-lactamase which can destroy the â-lactam ring and cause resistance to the other â-lactam antibiotics, such as amoxycillin. Extended spectrum â-lactamase (ESBL), an enzyme found in bacterial plasmids, is capable of hydrolyzing third-generation cephalosporins, namely cefotaxime, ceftazidime, ceftriaxone, and the monobactams. ESBL is predominantly found in Klebsiellas spp., Escherichia coli and other bacteria of the Enterobacteriaceae family. This study was conducted to determine the prevalence of Klebsiella resistant to cephalosporins and the prevalence of those producing ESBL. A total of 65 clinical isolates of Klebsiella were tested by the disk diffusion method according to Kirby-Bauer to determine their antibiotic susceptiblity and by the double-disk synergy method to detect the presence of ESBL. The results show that 18.5% of Klebsiella isolates tested were resistant to ceftazidime and cefixime, 13.9% to ceftriaxone, and 23.1% to aztreonam. Testing for ESBL revealed that the prevalence of ESBL producers in clinical Klebsiella isolates ranged from 10.8% to 12.3%. The presence of ESBL, plus the potential for plasmid-mediated quinolone and carbapenem resistance, undoubtedly will create significant therapeutic problems in the future.